2022
DOI: 10.1287/orsc.2021.1510
|View full text |Cite
|
Sign up to set email alerts
|

Going Along to Get Ahead: The Asymmetric Effects of Sexist Joviality on Status Conferral

Abstract: Social status is highly consequential in organizations but remains elusive for many professional women. Status characteristics theory argues that women are particularly status disadvantaged in masculine organizational cultures. These types of cultures valorize traits and abilities stereotypically associated with men, making it difficult for women in these settings to be seen as skilled and gain status. In the present study, we build and test novel theory explaining when and why masculine organizational culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…For instance, Cheryan and Markus's (2020) work on “masculine defaults” shows that men who fail to adhere to masculine norms are often informally sanctioned. Alonso and O'Neill (2021) demonstrate that women who successfully navigate masculine cultures by participating in them are perceived as savvy and socially skilled and accrue status as a result, while men who participate do not accrue the same status benefits. Our study extends extant research, demonstrating that men are not always the beneficiaries of cultures dominated by masculine norms by demonstrating that MCC can negatively impact men and their perceptions of procedural justice and that men who do not fully adhere to the masculine defaults or who choose to behave outside these norms are penalized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Cheryan and Markus's (2020) work on “masculine defaults” shows that men who fail to adhere to masculine norms are often informally sanctioned. Alonso and O'Neill (2021) demonstrate that women who successfully navigate masculine cultures by participating in them are perceived as savvy and socially skilled and accrue status as a result, while men who participate do not accrue the same status benefits. Our study extends extant research, demonstrating that men are not always the beneficiaries of cultures dominated by masculine norms by demonstrating that MCC can negatively impact men and their perceptions of procedural justice and that men who do not fully adhere to the masculine defaults or who choose to behave outside these norms are penalized.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research notes that a full understanding of gender dynamics requires richer insight into the experiences of men and that “a lack of understanding of men leaves us unable to account for everyday observations” (Mazei et al, 2021, p. 108) at work. While studies on masculinity are emerging (e.g., Alonso & O'Neill, 2021), less research examines how MCC affect men.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the moderate unit display requirements found to be optimal for authenticity and well‐being by Christoforou and Ashforth (2015) may permit flexibility to show negative emotions in encounters where mistreatment is occurring, thus breaking the cycle. Beyond this, one must also ask how strongly positive organizational emotional cultures (e.g., positive affective climate where any negativity is discouraged, Parke & Seo, 2017; culture of sexist joviality, Alonso & O'Neill, 2022) perpetuate sexist behaviors and play a harmful role, versus a companionate love culture (Barsade & O'Neill, 2014) that may shift positive treatment of others to a culture's core.…”
Section: The Future Decades Of Emotional Labor Research (2023 and Bey...mentioning
confidence: 99%
“…Unfortunately, it does pay to be sexist; research shows that those who hold sexist views incur more positive advantages in the workplace (e.g., more promotions) than less sexist colleagues (Watkins et al., 2006). This is so even for women who, by participating in the sexist culture, receive status benefits (Alonso & O'Neill, 2022). Locke et al.…”
Section: Men‐toring: Maintaining and Reproducing The Status Quomentioning
confidence: 99%
“…Unfortunately, it does pay to be sexist; research shows that those who hold sexist views incur more positive advantages in the workplace (e.g., more promotions) than less sexist colleagues (Watkins et al, 2006). This is so even for women who, by participating in the sexist culture, receive status benefits (Alonso & O'Neill, 2022). Locke et al (2021) found that women academics who were successful in leveraging opportunities in this neoliberal masculinist landscape, do so by reproducing "existing structures and inequalities in the university" (p. 1093).…”
Section: Mckinney Et Al (mentioning
confidence: 99%